Padi Liar Tetua Toleran Kekeringan - Didi Suwardi; Buang Abdullah (Buletin Plasma Nutfah, 2003)
AbstractDrought is one of the abiotic constraint in rice production, which occured during plant growth. Wild rice with drought tolerance charactes may be expected to contribute drought tolerance in modern rice varieties. The study was conducted in green house of Indonesian Agricultural Biotechnology and Genetic Resources Research Institute in DS 2002. About 87 wild rice accessions were treated in PEG 8000 solution and planted in pots experiment with wax-petrolatum layer as base of pots to identified osmotic potential and root penetration ability of seedlings. The experiment was arranged randomized block design with three replications. The result of the experiment showed that only two accession of Oryza glaberrima and O. nivara were sprouted in 32.5% conc. of PEG 8000 solution. Root penetration ability of the wild rice were recorded i.e. O. glumaepatula, O. glaberrima, O. nivara, O. punctata, and O. rufipogon. O. glaberrima 101297 is expected to be the one of the best wild rice accession for drought tolerant, beside its shortest maturity date and having good characters.AbstrakKekeringan merupakan kendala produksi padi dan dapat terjadi selama pertumbuhan tanaman. Padi liar yang mempunyai sifat toleran kekeringan diharapkan dapat dijadikan sebagai tetua dalam persilangan. Penelitian dilakukan di rumah kaca, Balai Penelitian Bioteknologi dan Sumberdaya Genetik Pertanian (Balitbiogen), Bogor MK 2002, untuk mendapatkan aksesi padi liar toleran kekeringan melalui uji daya osmotik perkecambahan dan daya tembus akar. Sebanyak 87 aksesi padi liar dikecambahkan dalam larutan PEG 8000 untuk uji daya osmotik. Uji daya tembus akar menggunakan lapisan lilin campuran parafin dan vaselin dengan ketebalan lapisan 3 mm di bagian bawah media tumbuh. Percobaan menggunakan rancangan acak kelompok dengan tiga ulangan. Hasil percobaan menunjukkan hanya dua aksesi padi liar Oryza glaberrima dan O. nivara yang mampu berkecambah pada larutan PEG 8000. Pada uji daya tembus akar diperoleh beberapa aksesi padi liar yang relatif sama daya tembusnya dengan IRAT 112, di antaranya O. glumaepatula, O. glaberrima, O. nivara, O. punctata, dan O. rufipogon. O. glaberrima 101297 memperlihatkan daya tembus yang hampir konsisten dari ketiga ulangan dengan penampilan tanaman pendek dan umur sangat genjah. O. glaberrima 101297 diharapkan dapat dijadikan tetua dalam program persilangan untuk perakitan padi toleran kekeringan dan umur genjah.